Manajemen Pasien Acute Fatty Liver Of Pregnancy (AFLP) di ICU - Handayani, Donna; Sari, Djayanti; Widyastuti, Yunita (Departemen Anestesi dan Terapi Intensif Fakultas Kedokteran UGM, 2015)
We reported management of patient in ICU of a woman aged 31 years, 50kg with a diagnosis of acute fatty liver of pregnancy (AFLP) post SC on fetal indications disstres. Patients previously treated on the ward obsgyn after the previous day into labor with cesarean section. Patients look weak, restless and jaundice, consulted the ICU with a diagnosis of post SC emergency dibangsal fi rst day on indications of fetal disstres, preterm, P2A0, sepsis with MODS. The patient is transported to the ICU with the support of oxygenation NRM O2 10 L / min. On the fi fth day in the ICU situation began to improve and steady, day-to-eight patients were allowed to move into the ward.